Associations between eyestrain and neck–shoulder symptoms among call-center operators - Wiholm, Clairy; Richter, Hans; Mathiassen, Svend Erik; Toomingas, Allan (SJWEH Supplements, 2007)
' ' OBJECTIVES ': 'Few, if any, studies have investigated whether eyestrain and shoulder–neck symptoms are correlated, although functional links could be expected on the basis of neurophysiological evidence. This cross-sectional study assessed correlations between self-reported eyestrain and shoulder–neck symptoms among call center workers, while controlling for possible confounders for these ailments. ' ' METHODS ': 'A questionnaire concerning socioeconomic background, work conditions, and symptoms was mailed to 1531 employees at 28 different call centers during 2001–2003. ' ' RESULTS ': 'Altogether 21% of the responding participants (N=1183) reported both eyestrain and neck–shoulder symptoms, 46% reported neck–shoulder symptoms only, and 6% reported eye symptoms only; 27% were free from symptoms in these regions. A significant positive association was found between eyestrain and neck–shoulder symptoms. Significant covariates for shoulder–neck disorders were eyestrain (OR 1.6, P=0.007), gender (to be female) (OR 1.9, P
Keywords: call-center; call-center operator; computer work; eye; eyestrain; neck; neck symptom; neck–shoulder symptom; operator; shoulder; shoulder symptom; strain; symptom